OPTIMIZATION OF SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEMS OF LEMONGRASS (CYMBOPOGON CITRATUS) ESSENTIAL OIL - Ujilestari, Tri; Ariyadi, Bambang; Martien, Ronny; ., Zuprizal; Dono, Nanung Danar (International Journal of Applied Pharmaceutics, 2019)
Objective: Focus of this study was to optimize and to characterize the self-Nano emulsifying drug delivery system using lemongrass (Cymbopogon citratus) essential oil. Methods: The optimum formulas were analyzed using a D-Optimal mixture experimental design and performed using a Design Expert® Ver. 7.1.5. Formulation variables which include in the design were: oil component X1 (a mixture of Cymbopogon citratus essential oil and virgin coconut oil/VCO), surfactant X2 (Tween 80), and co-surfactant (PEG 400), while emulsification time in a sec (Y1) and transmittance in percent (Y2) as responses. Results: The optimum formula for SNEDDS in the current study were: Cymbopogon citratus essential oil (7.147%), VCO (7.147%), Tween 80 (71.417%), and PEG 400 (14.290%). From the optimizing formula can be shown that the mean of droplet size, polydispersity-index, zeta potential, and viscosity were: 13.17±0.06 nm, 0.17±0.05,-20.90±1.47 mV, 200±0mPa. s (n=3), respectively. Furthermore, the optimized formula has passed the thermodynamic stability test; meanwhile, transmission electron microscopy displayed spherical shape. Conclusion: The optimized SNEDDS formula was improving solubility of poorly soluble Cymbopogon citratus essential oil.